2015
DOI: 10.1007/s11552-015-9764-9
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Signal Changes in the Extensor Carpi Ulnaris on MRI

Abstract: Background Magnetic resonance imaging (MRI) commonly finds musculoskeletal abnormalities incidental to the reason for ordering the test. The purpose of this study was to determine if the prevalence of extensor carpi ulnaris (ECU) signal changes on MRI varies between patients undergoing upper extremity MRI for assessment of clinically suspected ECU tendinopathy and those undergoing upper extremity MRI for other indications. Our secondary null hypotheses were that the prevalence of ECU signal changes on MRI does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
2
13
1
Order By: Relevance
“…Interestingly, three patients had an operation due to clinical examination on ECU pathology, which was not confirmed on MRI. This is consistent with a large multivariable analysis that revealed that ECU signal changes are common in the absence of clinical diagnosis and that nearly half of patients with a clinical diagnosis had no signal changes [12]. This indicates that MRI is only of limited use in evaluating ECU pathology.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, three patients had an operation due to clinical examination on ECU pathology, which was not confirmed on MRI. This is consistent with a large multivariable analysis that revealed that ECU signal changes are common in the absence of clinical diagnosis and that nearly half of patients with a clinical diagnosis had no signal changes [12]. This indicates that MRI is only of limited use in evaluating ECU pathology.…”
Section: Discussionsupporting
confidence: 86%
“…9,10 Studies on asymptomatic wrists have demonstrated a high rate of incidental TFCC findings, extensor carpi ulnaris pathology, and ganglia. [11][12][13] Multiple conditions, including ligament tears and Preiser disease, could be better imaged with gadolinium-enhanced MR arthrograms rather than routine MR alone. 9,14 MRI can be useful to detect occult carpal bone fractures, but treatment may be unnecessary if they are not visible on CT or radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…MRI can be useful for visualization of ECU tendinitis or confirmation of other soft tissue abnormalities such as scapholunate ligament or TFCC tears. 17 Dynamic ultrasound is an effective method for identification of ECU subluxation. 18-20 These differing findings highlight the clinical importance of performing the ECU Synergy Test prior to selecting an imaging modality, in an effort to gain information about injury type and minimize the unnecessary use of imaging studies.…”
Section: Wrist Injuriesmentioning
confidence: 99%